Basic statements on the security model for asymmetric transformations of the ES type taking into account the requirements and threats of the post-quantum period - Горбенко, Ю.І.; Потій, О.В.; Онопрієнко, В.В.; Єсіна, М.В.; Малєєва, Г.А. (Radiotekhnika, 2020)
The paper presents the results of substantiation and development of proposals for building a threat model for asymmetric cryptotransformations such as a promising electronic signature (ES), which can be used in the post-quantum period. The generalized models of threats concerning perspective ES are stated in detail and their estimation is given. Threat models for promising ES using classical and quantum cryptanalysis methods and tools, threat models for synthesis and application of ES in general, as well as threat models for synthesis and application of ES in the post-quantum period are proposed. Proposals are formulated for a list of threats for which protection should be provided. The list of possible security threats to existing and future ES is formed from the number of threats available in IT-Grundschutz Catalogs, taking into account hardware, software and hardware-software resources, data processing technologies and cryptographic protection mechanisms in the use of ES, including requirements and conditions of synthesis of promising ES and application of ES in the post-quantum period. The concepts of EUF-CMA and SUF-CMA security are considered. Algorithms of work of each of these schemes are given. The concept of a comprehensive security model is introduced and its components are presented. The model of the violator and its essence are considered. The main threats (attacks) are given using quantum mathematical methods that can be implemented on a quantum computer (of course, if it is built and available for use). Attacks (threats) against a promising ES are presented and considered. The analysis of signature schemes for compliance with the required security models is performed. The terms "forward secrecy" and "perfect forward secrecy" are introduced and used. An analysis of signature schemes that are EUF-CMA and SUF-CMA secure is performed. Signature schemes, that are key-dependent, with evolving keys, are considered in terms of compliance with the EUF-CMA or SUF-CMA security model. The stateless signature algorithm is also considered. Algorithms of operation of such signature schemes are given.